Restorative justice: theoretical foundations - Weitekamp, Elmar G. M.; Kerner, Hans-Jürgen (Willan Pub, 2002)
This book brings together a selection of papers originally presented and discussed at the fourth international restorative justice conference, held at the University of Tübingen. The contributors include many of the leading authorities in the field of restorative justice, and they provide a comprehensive review of the theoretical foundations underlying this rapidly expanding movement. Restorative Justice: Theoretical foundations addresses a wide range of fundamental questions about restorative justice, considering amongst other things ways in which conceptual pitfalls can be avoided, and how t